Theory and Practice: A Matter of Words. Language, Knowledge and Professional Community in Social Work - Silvia Fargion (Social Work and Society)
The relation between theory and practice in social work has always been controversial. Recently, many have underlined how language is crucial in order to capture how knowledge is used in practice. This article introduces a language perspective to the issue, rooted in the 'strong programme' in the sociology of knowledge and in Wittgenstein's late work. According to this perspective, the meaning of categories and concepts corresponds to the use that concrete actors make of them as a result of on-going negotiation processes in specific contexts. Meanings may vary dramatically across social groups moved by different interests and holding different cultures. Accordingly, we may reformulate the issue of theory and practice in terms of the connections between different language games and power relationship between segments of the professional community. In this view, the point is anyway to look at how theoretical language relates to practitioners' broader frames, and how it is transformed while providing words for making sense of experience.